Combustion synthesis, characterization and luminescence properties of barium aluminate phosphor - Wako, Ali Halake; Dejene, F. B.; Swart, H.C. (Elsevier, 2014)
The blue-green emitting Eu2+ and Nd3+ doped polycrystalline barium aluminate (BaAl2O4:Eu2+,Nd3+) phosphor, was prepared by a solution-combustion method at 500 °C without a post-annealing process. The characteristic variation in the structural and luminescence properties of the as-prepared samples was evaluated with regards to a change in the Ba/Al molar ratio from 0.1:1 to 1.4:1. The morphologies and the phase structures of the products were characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS), while the optical properties were investigated using ultra-violet (UV) and photoluminescence (PL) spectroscopy, respectively. The XRD and TEM results revealed that the average crystallite size of the BaAl2O4:Eu2+,Nd3+ phosphor was about 70 nm. The broad-band UV-excited luminescence of the phosphors was observed at λmax=500 nm due to transitions from the 4f65d1 to the 4f7 configuration of the Eu2+ ion. The PL results indicated that the main peaks in the emission and excitation spectrum of phosphor particles slightly shifted to the short wavelength due to the changes in the crystal field due to the structure changes caused by the variation in the quantity of the Ba ions in the host lattice.
The authors are immensely grateful to the Prestige Cluster Bursary Program of the University of the Free State for financial support towards this project. The authors also thank the University of the Free State Physics Department for assistance with the research technique systems used to characterize materials for this study. DOI: 10.1016/S1002-0721(14)60145-9
Keywords: BaAl2O4:Eu2+; Nd3+; persistence luminescence; Eu2+ and Nd3+ doping; rare earths